Globalisation and rural poverty in Latin America: modelling the links to soil degradation. (1st January 2000) - Binder, Claudia; Lopez, Ramon
The main objective of this paper is to present a framework to evaluate the impact of globalisation on poor farmers. We present a dynamic ecological-economic model that can be used to quantify the impact of globalisation on farmers' income and the quality of their natural resource base. The model combines material flux analysis with economic behavioural relationships. It allows for: (i) measuring the "direct" or short-term effects of globalisation on poor farmers' income (given the level of environmental factors of production, and differentiating between male and female labour allocation); (ii) quantifying the environmental impacts induced by globalisation (including changes in the environmental factors of production); and (iii) measuring the effects of changes in environmental factors on poor farmers' income, i.e. the "indirect" or long-term effects.